Perkawinan Childfree dalam Perspektif Hukum Islam - Habibi, Jk; Ma'arif, Khoirul; Putra, Adji Pratama; Burhanusyihab, Agung (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
This research examines childfree marriage in the perspective of Islamic Law. Childfree is an agreement made by a husband and wife not to have children during their marriage. This study aims to determine how childfree marriage is in the view of Islamic law. This research uses library research with a normative approach. With a normative approach to the Qur'an and Sunnah, it can be seen that having offspring is a recommendation in Islam, not an obligation. Therefore, childfree is not a prohibited act, because every person or married couple has the right to plan and organize their household including in terms of choosing to have children or not. Although there is no verse that directly prohibits childfree, as a human being who believes in the existence of Allah SWT, the choice to be childfree is an unwise choice because Allah SWT guarantees the survival of all his servants. Islam views that children are a gift from Allah SWT that must be grateful for. Every human being who is given the mandate to become a parent must fulfill their role well and in totality for their children. Childfree is used by the community to refer to childless marriages. Textually there is no Nash verse that prohibits the choice to be childfree